Mechanisms for ·O2- and ·OH Production on Flowerlike BiVO4 Photocatalysis Based on Electron Spin Resonance - Xu, Xuan; Sun, Yaofang; Fan, Zihong; Zhao, Deqiang; Xiong, Shimin; Zhang, Bingyao; Zhou, Shiyu; Liu, Guotao (Frontiers in Chemistry, 2018)
Many studies have focused on the use of BiVO4 as a photocatalyst, but few have investigated the production of free radicals during the photocatalytic process. Following synthesis of flowerlike BiVO4 and characterization by X-ray diffraction (XRD), Raman spectroscopy, Scanning electron microscopy (SEM) Scanning electron microscopy (EDX), UV-Vis and XPS, we successfully prepared BiVO4. Then we used electron spin resonance (ESR) to determine the production and degradation of individual active free radicals, including the superoxide radical (•O2−) and the hydroxyl radical (•OH). In the first experiment, we used ESR to detect the signals of free radicals (•O2− and •OH) under varying oxygen conditions. The results shown that in addition to production by •O2−, •OH could also be produced by oxidation of h+ to OH−. In the next experiment, we detected •OH under varying pH to identify the result of the first experiment, and found that signal intensities increased with increasing pH, indicating the mechanism for •OH production. Finally, we conducted a trapping experiment to examine free radical degradation mechanisms. We identified •OH and h+ as the main active free radicals and showed the complete production about •OH. These results improve current knowledge of free radical production mechanisms, which can be used to enhance the photocatalytic performance of BiVO4.